The effects of xanthan gum and hydroxypropylmethylcellulose on physical properties of sponge cakes - A. Noorlaila; H. Nor Hasanah; R. Asmeda; A. Yusoff (Journal of the Saudi Society of Agricultural Sciences)
The effect of xanthan gum (XG) and hydroxypropylmethylcellulose (HPMC) on cake volume, hardness and sensorial properties of baked sponge cakes were investigated. The rheological characteristics which consist of flow behaviour and viscoelasticity of batter were also investigated to relate with the physical properties of sponge cake. Batter density and specific gravity were significantly (p < 0.05) correlated with hardness and volume of cake. Hydrocolloids cakes (both XG and HPMC) had significantly (p < 0.05) lower volume compared to control cake. Consistency index was significantly (p < 0.05) correlated with hardness (rConsistency index = 0.71) which able to determine the crumb texture of sponge cake. The freshly baked cake containing 1% XG has significantly (p < 0.05) higher value of hardness compared to 1% HPMC and control cakes. In addition, sponge cake containing hydrocolloids had significantly (p < 0.05) lower volume compared to control cake. For sensory evaluation, sponge cake containing xanthan gum was less preferred by the panellists compared to other sponge cake formulations since it presented lowest mean score in overall acceptability (6.25). Keywords: Hydrocolloid, Viscosity, Hardness, Volume, Batter